The prognosis of brain magnetic resonance imaging injury pattern for outcomes of hypothermia-treated infants. Issue 48 (25th November 2020) - Seo, Yu-Mi; Im, Soo-Ah; Sung, In Kyung; Youn, Young Ah
Abstract : Abstract: Magnetic resonance imaging (MRI) can be a tool that allows the observation of structural injury patterns after cooling. The aim of this study was to determine the early pattern of brain injury in the MRIs of infants with hypoxic ischemic encephalopathy (HIE) after cooling and to search for any clinical factors related to abnormal MRI findings. The study retrospectively recruited 118 infants who were treated with therapeutic hypothermia (TH) between 2013 and 2016. Forty-three patients had normal brain MRI, and 75 had abnormal brain MRI findings. The TH-treated infants with abnormal brain MRI readings showed significantly more clinical seizures and the use of additional antiepileptic drugs (AEDs) than the normal MRI group. As a long-term outcome, more lesions in the basal ganglia and thalamus, posterior limb of internal capsule, or severe white matter lesions were associated with abnormal neurodevelopmental outcomes at 18 to 24 months of age. A higher frequency of clinical seizures and AED use were related to abnormal brain injury on MRI. A significant risk for poor long-term outcomes was found in the abnormal brain MRI group.